Predictors of reinfection with pre-Omicron and Omicron variants of concern among individuals who recovered from COVID-19 in the first year of the pandemic - Dani Cohen; Marina Izak; Evgeniy Stoyanov; Michal Mandelboim; Saritte Perlman; Yonatan Amir; Sophy Goren; Anya Bialik; Limor Kliker; Nofar Atari; Ruti Yshai; Yona Zaide; et al. (International Journal of Infectious Diseases, 2023)
Objectives: The predictors of SARS-CoV-2 reinfection are unclear. We examined predictors of reinfection with pre-Omicron and Omicron variants among COVID-19-recovered individuals. Methods: Randomly selected COVID-19-recovered patients (N = 1004) who donated convalescent plasma during 2020 were interviewed between August 2021 and March 2022 regarding COVID-19 vaccination and laboratory-proven reinfection. The sera from 224 (22.3%) participants were tested for antispike (anti-S) immunoglobulin G and neutralizing antibodies. Results: The participants’ median age was 31.1 years (78.6% males). The overall reinfection incidence rate was 12.8%; 2.7% versus 21.6% for the pre-Omicron (mostly Delta) versus Omicron variants. Negative associations were found between fever during the first illness and pre-Omicron reinfection: relative risk 0.29 (95% confidence interval 0.09-0.94), high anti-N level at first illness and Omicron reinfection: 0.53 (0.33-0.85), and overall reinfection: 0.56 (0.37-0.84), as well as between subsequent COVID-19 vaccination with the BNT162b2 vaccine and pre-Omicron 0.15 (0.07-0.32), Omicron 0.48 (0.25-0.45), and overall reinfections 0.38 (0.25-0.58). These variables significantly correlated with immunoglobulin G anti-S follow-up levels. High pre-existing anti-S binding and neutralizing antibody levels against the SARS-CoV-2 Wuhan and Alpha strains predicted protection against Omicron reinfections. Conclusion: Strong immune responses after the first COVID-19 infection and subsequent vaccination with the BNT162b2 vaccine provided cross-protection against reinfections with the Delta and Omicron variants.